Periodic table in style of spiral with radii - Tocher, J. F. (James Fowler); Mazurs, Edward G. (1910)
Graphic representation of the periodic table of chemical elements in the style of a spiral with radii and interrupted short periods. This table was originated by Scottish chemist James Fowler Tocher (1864-1945) in 1910 and classified by chemist Edward G. Mazurs as Type IIB2-3 in his seminal work Types of Graphic Representation of the Periodic System of Chemical Elements (1957). This table appears as Figure 52 on page 125 of Mazurs' 1957 publication.
Keywords: Scientific illustration; Tocher, J. F. (James Fowler), 1864-; Periodic table of the elements; Periodic law; Chemical elements